(untitled) (San Francisco, 1996)
Leading-Edge Thought From the World's Best Business Minds "A one-stop shopping guide that shows how leaders can be successful in the year 2000 and beyond." --American Society for Training and Development Discover what Stephen Covey, Ken Blanchard, Peter Senge, Rosabeth Moss Kanter, and other business-world luminaries have to say about the direction of leadership for the future. The Drucker Foundation brings together the best business minds in more than 30 never-before-published essays, each one offering a special perspective on leadership and a unique glimpse into the future.
Keywords: Leadership,Strategic planning,Lãnh đạo,Kế hoạch chiến lược